Developing BIOTEL: A Semi-Automated Spreadsheet for Estimating Telomere Length and Biological Age - Tsatsakis, Aristidis; Tsoukalas, Dimitrios; Fragkiadaki, Persefoni; Vakonaki, Elena; Tzatzarakis, Manolis; Sarandi, Evangelia; Nikitovic, Dragana; Tsilimidos, Gerasimos; Alegakis, Athanasios K. (Frontiers in Genetics, 2019)
Background: Telomere length (TL) is causally related to aging and several age-related diseases. Specifically, the abundance of short telomeres and the rate of telomere shortening are strong determinants of cell homeostasis. Thus, tools for analyzing and manipulating TL data can vastly improve research focused on aging. Aim: In this study, we developed a semi-automated worksheet, BIOTEL, to generate individual and group TL statistics and provide a crude estimation of biological age. Results: Data from the Telomere Length Database Project (TLDP) were implemented to the spreadsheet to produce TL statistics. 150 participants were included, and their age was from 21 to 82 years, and the sex distribution ratio was 52.3%: 47.7% (male: female). Initially, we analyzed the fluorescence intensities of telomeres that were measured on metaphase spread leukocytes using three-dimensional (3D)quantitative-fluorescent in situ hybridization (Q-FISH) procedures (3D DNA FISH) with a (C3TA2)3 peptide nucleic acid (PNA) probe. Raw data of fluorescence intensities, demographic data and medical records from the participants were imported into the worksheet. Basic statistical analyses of TL data were provided through BIOTEL, including TL percentiles, specialized charts for TL distribution including the percentage of critically short telomeres (<3,000kilobases), individual telomere profiles,and graphs of biological age vs. chronological age. Conclusions: BIOTEL ver. 2.4 is a functional semi-automated worksheet that calculates a wide range of TL statistics, thus a useful tool with applications in research of telomeres and biological age estimation.